Predictors in profile of referred newborns for their outcome in a tertiary newborn referral facility - Verma, Avadhesh; Gaur, Ajay; Ambey, Ravi (International Journal of Contemporary Pediatrics, 2018)
Background: This study was aimed to assess newborn referral and factors contributing to outcome of referred newborns. Methods: This prospective observational study was conducted in a tertiary newborn referral facility for a period of one year. Referred newborns fulfilling inclusion criteria were enrolled in study, and assessed in terms of demographic profile, transport characteristics, physiological variables. Investigations, management of neonatal illness was done as per standard management protocols, they were followed up to their outcome. Results: Out of 2000 enrolled referred newborns, 30.10% were expired. Mean gestational age for survived newborns was 36.54±2.92 (SD) weeks, for expired newborns 35.24±3.99 (SD) weeks. Mean weight for survived newborns 2312.27 gms ±555.71 (SD), for expired newborns 1936.71 gms ±665.67 (SD). Out of total 60.05% newborns transported from periphery, had higher mortality i.e. 35% as compared to newborns transported from urban place i.e. 25%. Mean transport duration for survived newborns 61.94 minutes ±55.18 (SD), for expired newborns 89.51 minutes ±88.94 (SD). Prolonged CRT was observed in 57.45% newborns, grunting 19.70%, Cyanosis 11%, gasping 7.6%, apnea 5%, respiratory distress 39.80%, hypothermia 74.95%, and 25.50% required resuscitation on admission. Unattended delivery, self-arranged mode of transport, prolonged CRT, respiratory distress, apnea , hypothermia on admission, weight on admission(<1500gms), hypoglycaemia and duration of transport more than 1 hour found statistically significant independent variables associated with mortality of referred newborns. Conclusions: A significant number of neonatal deaths can be prevented, if referral system is structured and organized. Improper referral leads to poor physiological profile of referred newborns, which leads to their poor outcome. There are many independent variables which are affecting the outcome of referred newborns. These independent variables can be taken care in holistic way once the referral system is cultured and nurtured in existing health system.